Consumers' Willingness to Pay for Low Pesticide Fresh Cabbage - Abira, S.; Sooriyakumar, K.; Sireeranhan, A. (University of Jaffna, 2008)
The purpose of this survey was to assess and determine consumers' perceptions of food safety and their attitudes toward use of pesticides in the production of pesticide low fresh cabbage. Vegetable plays important roles in the socio-economic development in Srilanka. Jaffna district is one of the high potential areas for agriculture production. Food safety has received increased attention in recent years as a major consumer concern. Cancer risk among agriculture population will improve health and safety among this important segment of the population. Agriculture is an occupation yielding substantial profit in the steady source of income for most of the people in the Jaffna peninsula. Pest management in Agriculture is mostly pesticide dependent and farmers are applying more than recommended level of pesticides to control pests. Over dosage of pesticide causes effects on Environmental components and human health. The data being collected for this study from the Jaffna district in which Kopay and Jaffna municipal area was considered to be a sample. A simple random sampling method was used to select 157 households for interviewing. Information was collected on consumer's habits, demographic characteristics and attitudes towards and knowledge of pesticide residual food products. Ordered probit model was developed for this analysis. Ordered probit regression is the more theoretically appropriate method for WTP data sets. The variables included in this analysis are monthly income of the household, education level of the respondent, whether the respondent feels pesticide residue products will cause cancer, whether the respondent red any articles from newspapers and magazines or hear that pesticide cause cancer, are used as explanatory variables. The dependent variable is the WTP to low pesticide residue fresh cabbage. Result of this study shows that the level of education, family income, respondent's perception and awareness regarding the harmful effect of pesticide positively influence the willingness to pay for low pesticide fresh cabbage at 5% significant level.